Islamiat lazmi class 9/10 - Dr ahsan-ul-haq (Punjab curriculum and textbook board Lahore, 2017)
Islamiat Lazmi Class 9/10 is a textbook designed to impart essential Islamic knowledge, teachings, and ethical values to students, helping them strengthen their faith and understanding of Islam.